2014
DOI: 10.1016/j.celrep.2014.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Restrains NHEJ through Phosphorylation of XRCC4-like Factor Xlf1

Abstract: SummaryEukaryotic cells use two principal mechanisms for repairing DNA double-strand breaks (DSBs): homologous recombination (HR) and nonhomologous end-joining (NHEJ). DSB repair pathway choice is strongly regulated during the cell cycle. Cyclin-dependent kinase 1 (Cdk1) activates HR by phosphorylation of key recombination factors. However, a mechanism for regulating the NHEJ pathway has not been established. Here, we report that Xlf1, a fission yeast XLF ortholog, is a key regulator of NHEJ activity in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…30 CDK1 activates HR by phosphorylating key recombination factors, and phosphorylates the XRCC4-like factor (XLF; also known as Cernunnos) to downregulate NHEJ, at least in yeast. 31 Repair is also linked to the cell cycle by Chk1, an effector kinase of ATR that promotes checkpoint arrest in S and G2/M, and DNA repair through RAD51 and HR. 32 Chk1 inhibition leads to DNA damage and cell death, 33 and is a potential target for improving the outcome of radiation therapy.…”
Section: Targeting Dna Damage and Repairmentioning
confidence: 99%
“…30 CDK1 activates HR by phosphorylating key recombination factors, and phosphorylates the XRCC4-like factor (XLF; also known as Cernunnos) to downregulate NHEJ, at least in yeast. 31 Repair is also linked to the cell cycle by Chk1, an effector kinase of ATR that promotes checkpoint arrest in S and G2/M, and DNA repair through RAD51 and HR. 32 Chk1 inhibition leads to DNA damage and cell death, 33 and is a potential target for improving the outcome of radiation therapy.…”
Section: Targeting Dna Damage and Repairmentioning
confidence: 99%
“…Several components of the NHEJ pathway have also been identified as targets of CDKs. However, CDK phosphorylation inhibits the recruitment of NHEJ factors, for instance, YKu70 (the yeast KU70 homolog) and Lif1 to DNA breaks in S. cerevisiae (Zhang et al, 2009) and XRCC4/XLF1 in S. pombe (Hentges et al, 2014). Thus, there appears to a reciprocal relationship between these two repair pathways where NHEJ is high in G1 and low in G2 phase, whereas HR is not possible in G1 and high in G2 phase (Ferreira & Cooper, 2004).…”
Section: Targets Of Cdk-cyc Complexes In Hr Versus Nhejmentioning
confidence: 99%
“…23 Similar to the cellular effects of our identified Akt-mediated XLF phosphorylation event in mammalian cells, Hentges et al demonstrated that phosphorylation of Xlf1 in fission yeast by Cdk1 inhibits NHEJ. 23 Hence, NHEJ can override HR when Cdk1-mediated Xlf1 phosphorylation is inhibited, arguing for a critical role of phosphorylation of XLF in suppression of NHEJ.…”
Section: 16mentioning
confidence: 56%
“…23 Similar to the cellular effects of our identified Akt-mediated XLF phosphorylation event in mammalian cells, Hentges et al demonstrated that phosphorylation of Xlf1 in fission yeast by Cdk1 inhibits NHEJ. 23 Hence, NHEJ can override HR when Cdk1-mediated Xlf1 phosphorylation is inhibited, arguing for a critical role of phosphorylation of XLF in suppression of NHEJ. Intrigued by the similar consequences of XLF phosphorylation events, we have aligned human XLF and fission yeast Xlf1 sequences and interestingly observed that neither the mammalian Akt site (Thr181), nor the yeast Cdk1 sites (Thr180 and Ser192) are conserved between these two species (Fig.…”
Section: 16mentioning
confidence: 56%